2016
DOI: 10.1002/adma.201600642
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Thermal Conductivity of Interface Materials by Silver‐Functionalized Carbon Nanotube Phonon Conduits

Abstract: An ultrahigh thermal conductivity (κ = 160 W m(-1) K(-1) ) of thermal interface materials is achieved with a high enhancement factor (96). A small amount (2.3 vol%) of 1D multiwalled carbon nanotubes (MWNTs) with high κ constructs effective phonon transport pathways between microscale silver-flake islands, and a solid phonon transport junction is realized by the coalescence of silver nanoparticles pre-functionalized on the MWNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
164
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(166 citation statements)
references
References 43 publications
2
164
0
Order By: Relevance
“…[60] Figure 9 presents the fabrication process of flexible thermoelectric generator (TEG) by screen printing. [64] For screen printing techniques, porous structures may be created during the printing process that can reduce the conductivity of printed parts. The authors demonstrated that the screen printing process helps to increase productivity of TEG.…”
Section: Screen Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…[60] Figure 9 presents the fabrication process of flexible thermoelectric generator (TEG) by screen printing. [64] For screen printing techniques, porous structures may be created during the printing process that can reduce the conductivity of printed parts. The authors demonstrated that the screen printing process helps to increase productivity of TEG.…”
Section: Screen Printingmentioning
confidence: 99%
“…[64,65] However, these techniques still lack the ability to adequately control, are time consuming, and limited to achieve large-scale production. Different alignment methods have been investigated, such as electrical flocking, magnetic field assisted alignment, and rolling.…”
Section: Future Of 3d Printing For Thermal Related Application Devicesmentioning
confidence: 99%
“…Thermal interface materials (TIMs) are usually placed between the heated device and the thermal sink to fill the air‐filled voids to efficiently improve the heat transmission . Polymer composites have attracted extensive attention as TIMs because of their pervasive application . Thermal grease is the most widely used TIMs that is composed of a polymer matrix and inorganic filers with high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For platelet-like or rodlike fillers with high aspect ratio such as natural graphite (NG), boron nitride (BN), carbon nanotube, silicon carbide (SiC), graphene, and so on, the thermal conductivity along the longitudinal direction of the fillers is usually much higher than that in the perpendicular direction. [1][2][3] For platelet-like or rodlike fillers with high aspect ratio such as natural graphite (NG), boron nitride (BN), carbon nanotube, silicon carbide (SiC), graphene, and so on, the thermal conductivity along the longitudinal direction of the fillers is usually much higher than that in the perpendicular direction.…”
Section: Introductionmentioning
confidence: 99%